A mountain of exchange - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The international conference of the African Mountains Association (AMA) will be held in mid August, 2002, in Moshi, Tanzania. It will address ways and means to promote the conservation and sustainable development of Africa s mountain resources.AMA,...